Are suspected stroke patients identified by paramedics transported to appropriate stroke centres in Victoria, Australia? - Bray, Janet; Coughlan, K.; Mosley, I.; Barger, B.; Bladin, C. (2014)
Emergency medical services (EMS) are vital to ensuring acute stroke patients are transported to thrombolysis and/or stroke unit centres. This 6-month audit of Victorian EMS cases found the majority of suspected acute strokes are transported to appropriate stroke centres. However, there is still room for improvement, in particular, strategies to improve access to stroke services in some rural regions and to ensure patients/relatives are fully informed when requesting transport to a non-stroke service hospital.